Update to RIFM fragrance ingredient safety assessment, cyclohexanecarboxylic acid, 1, 4-dimethyl-, methyl ester, trans-, CAS registry number 23250-42-2. (September 2022) - Api, A.M.; Belsito, D.; Botelho, D.; Bruze, M.; Burton, G.A.; Cancellieri, M.A.; Chon, H.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; Fryer, A.D.; et al.
Highlights: Cyclohexanecarboxylic acid, 1, 4-dimethyl-, methyl ester, trans-; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.